Assessing Pigment-Based Phytoplankton Community Distributions in the Red Sea - Kheireddine, Malika; Ouhssain, Mustapha; Claustre, Hervé; Uitz, Julia; Gentili, Bernard; Jones, Burton H. (Frontiers in Marine Science, 2017)
Pigment-based phytoplankton community composition and primary production were investigated for the first time in the Red Sea in February-April 2015 to demonstrate how the strong south to north environmental gradients determine phytoplankton community structure in Red Sea offshore regions (along the central axis). Taxonomic pigments were used as size group markers of pico, nano- and microphytoplankton. Phytoplankton primary production rates associated with the three phytoplankton groups (pico-, nano- and microphytoplankton) were estimated using a bio-optical model. Pico- (Synechococcus and Prochlorococcus sp) and Nanophytoplankton (Prymnesiophytes and Pelagophytes) were the dominant size groups and contributed to 49% and 38%, respectively, of the phytoplankton biomass. Microphytoplankton (diatoms) contributed to 13% of the phytoplankton biomass within the productive layer (1.5 Zeu). Sub-basin and mesoscale structures (cyclonic eddy and mixing) were exceptions to this general trend. In the southern Red Sea, diatoms and picophytoplankton contributed to 27% and 31% of the phytoplankton biomass, respectively. This result induced higher primary production rates (430 ± 50 mgC m-2 d-1) in this region (opposed to CRS and NRS). The cyclonic eddy contained the highest microphytoplankton proportion (45% of TChla) and the lowest picophytoplankton contribution (17% of TChla) while adjacent areas were dominated by pico- and nanophytoplankton. We estimated that the cyclonic eddy is an area of enhanced primary production, which is up to twice those of the central part of the basin. During the mixing of the water column in the extreme north of the basin, we observed the highest TChla integrated (40 mg m-2) and total primary production rate (640 mgC m-2 d-1) associated with the highest nanophytoplankton contribution (57% of TChla). Microphytoplankton were a major contributor to total primary production (54%) in the cyclonic eddy. The contribution of picophytoplankton (Synechococcus and Prochlorococcus sp) reached maximum values (49%) in the central Red Sea. Nanophytoplankton seem to provide a ubiquitous substantial contribution (30-56%). Our results contribute to providing new insights on the spatial distribution and structure of phytoplankton groups. An understanding and quantification of the carbon cycle in the Red Sea was made based on estimates of primary production associated with pico-, nano- and microphytoplankton.